2012
DOI: 10.1039/c2nr31167d
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional nanoarchitectonics: organic and hybrid materials

Abstract: Programmed molecular assemblies with molecular-level precision have always intrigued mankind in the quest to master the art of molecular engineering. In this regard, our review seeks to highlight the state of the art in supramolecular engineering. Herein we describe two-dimensional (2D) nanoarchitectonics of organic and organic-inorganic based hybrid materials. Molecular systems ranging from simpler hydrogen bonding driven bis-acylurea and cyclic dipeptide derivatives to complex peptoids, arylenes, cucurbituri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 94 publications
0
97
0
Order By: Relevance
“…10 The 2D organic crystal system is an ideal system to study the optical and electronic properties. [10][11][12][13] However, compared to the extensive studies of 1D nanostructures, the investigations of large-size 2D The inset of (a) is the chemical structure of BPEA molecule. The inset of (c) is an SEAD pattern recorded within a single nanosheet.…”
Section: Nanosheets Show Obvious Light Emission Anisotropymentioning
confidence: 99%
“…10 The 2D organic crystal system is an ideal system to study the optical and electronic properties. [10][11][12][13] However, compared to the extensive studies of 1D nanostructures, the investigations of large-size 2D The inset of (a) is the chemical structure of BPEA molecule. The inset of (c) is an SEAD pattern recorded within a single nanosheet.…”
Section: Nanosheets Show Obvious Light Emission Anisotropymentioning
confidence: 99%
“…The 2D sheet architecture emphasizes the fact that the tendency for molecular assembly (strength of intermolecular interactions) of 1 along its length and breadth is nearly equal. Although there is no clear demarcation between sheets and short belt‐like architectures, we had earlier proposed that an aspect ratio (length to breadth) of ≀10 corresponds to sheets, based on reports in the literature 2b. Atomic force microscopy (AFM) revealed that the topographical thickness (height) of these sheets is in the range of 20–50 nm 9.…”
Section: Resultsmentioning
confidence: 99%
“…Organic nanocrystals are formed by the periodic packing of organic molecules in the nanometer range, which have attracted increasing attentions for their potential applications in flexible electronics and nanophotonics through the discovery of new properties and nanoeffects . Additionally, organic nanocrystals, especially 2D nanosheets, are expected to be the major components of eco‐friendly aqueous inks to fabricate film devices in printed optoelectronics. In this assembly process, they act as the intermediate to bridge the interval between molecules and film devices under the frameworks of hierarchical chemistry .…”
Section: Introductionmentioning
confidence: 99%